(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2022)
This article gives a brief account of how Breath-Figures (BF) are used as a dynamic templating method to prepare periodic nanostructures in sizes ranging from nanometers to micrometers. Although a defined, exact mechanism for BF formation is not yet known, literature surveys do conclude some important overviews. The formation of honeycomb structures, quasi-crystalline arrays, hexagonal arrays and highly ordered BFs of different shapes and pore sizes are summarized.